2002
DOI: 10.1164/rccm.200202-075oc
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory Muscle Training in Patients with Chronic Obstructive Pulmonary Disease

Abstract: The present study was aimed at evaluating the effects of a specific inspiratory muscle training protocol on the structure of inspiratory muscles in patients with chronic obstructive pulmonary disease. Fourteen patients (males, FEV1, 24 +/- 7% predicted) were randomized to either inspiratory muscle or sham training groups. Supervised breathing using a threshold inspiratory device was performed 30 minutes per day, five times a week, for 5 consecutive weeks. The inspiratory training group was subjected to inspira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
208
2
14

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(238 citation statements)
references
References 41 publications
14
208
2
14
Order By: Relevance
“…Previous studies have shown that such interventions lead to improvements in physical conditioning and muscle strength of children with asthma, as was confirmed in our study. (20) The results of the present study are in agreement with those of studies involving adults diagnosed with obstructive diseases, (2,8,9,21,22) showing improvements in respiratory muscle strength, with consequent clinical improvement, after specific IMT.…”
Section: Resultssupporting
confidence: 90%
“…Previous studies have shown that such interventions lead to improvements in physical conditioning and muscle strength of children with asthma, as was confirmed in our study. (20) The results of the present study are in agreement with those of studies involving adults diagnosed with obstructive diseases, (2,8,9,21,22) showing improvements in respiratory muscle strength, with consequent clinical improvement, after specific IMT.…”
Section: Resultssupporting
confidence: 90%
“…Improvement of muscle tonus by physical training has been shown on several studies, and they were based on exercises for endurance and strength properties. This improvement was associated with increases in the proportion of Type I fiber and in the size of Type II fiber, demonstrated by muscle biopsy samples [42][43][44][45][46][47][48][49][50][51][52][53] . Methods to increase muscle tonus of the stomatognathic system are based on gain of endurance and strength properties either, so we considered this option as a possibility to increase the proportion of fiber Type I, resulting in decrease of snoring and clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…We know much more now about the pathogenesis of snoring and obstrutive sleep apnea (OSA), and some studies brought us evidences that the muscles in the pharynx are affected, showing fiber desproportion [38][39][40][41] . Based on such information, would be interesting to search for studies that have treated patients aiming to interfere with a diseased upper airway through out any sort of physical intervention to increase muscle tonus [42][43][44][45][46][47][48][49][50][51][52][53] . The aim of this systematic review is to evaluate if methods to increase muscle tonus of the upper airway is effective and safe for treatment of snoring based on accepted scientific evidence.…”
Section: Dr Gilmar Fernandes Do Prado -Rua Claudio Rossi 394 -01547-mentioning
confidence: 99%
“…These measurements serve for the evaluation of maximum strength. Currently, only one device for evaluating respiratory muscle endurance is available commercially, even though this is the property that is most susceptible to changes following specific training programs 56 . It is now known that identifying the strength of the respiratory muscles, and particularly the strength of the inspiratory muscles, is of fundamental importance in determining whether inspiratory muscle training (IMT) should be included in rehabilitation programs.…”
Section: Evaluation Of Respiratory Muscle Strengthmentioning
confidence: 99%